Dynamis eis Soterian: Investigating the Semantic Background of a New Testament Syntagma - Hauck, Marion (Novum Testamentum, 2019)
This study shows that the syntagma δύναµις εἰς σωτηρίαν was widely used in ancient Greek literature of the Classical, Hellenistic, and Greco-Roman periods. A semantic context analysis reveals that "danger" is the common intersection of all contexts in which the syntagma δύναµις εἰς σωτηρίαν occurs. In a modified way it also appears in texts of the New Testament (Rom 1:16; 1 Pet 1:5): By using δύναµις (θεοῦ) εἰς σωτηρίαν in a context focused on danger, Paul (as well as the author of 1 Peter) indicates that his use of the syntagma is consistent with the pagan, non-biblical use of δύναµις εἰς σωτηρίαν.